Olfactory receptors in the melon fly Dacus cucurbitae and the oriental fruit fly Dacus dorsalis - Metcalf, Robert L. (1983)
Male melon flies (Dacus cucurbitae) from a colony in Hawaii were evaluated for limit of response to the olfactory stimulant raspberry ketone and to more than 40 related molecules. The results were compared with the limits of response of oriental fruit flies (Dacus dorsalis) under identical conditions. The nature of the response of the two species to attractive compounds appeared to be identical with regard to orientation, searching, pulsating mouthparts, and compulsive feeding. However, there was very little overlap in the response of the two species to phenylpropanoid-type compounds. D. cucurbitae responded most strongly to p-hydroxyphenylpropanoids while D. dorsalis responded most strongly to 3,4-dimethoxyphenylpropanoids. The results are discussed in terms of antennal receptor site geometry and with regard to the coevolution of two major groups of Dacini with plant kairomones.